Research and development of hydrogen carrier based solutions for hydrogen compression and storage. (1st October 2022) - Dornheim, Martin; Baetcke, Lars; Akiba, Etsuo; Ares, Jose-Ramón; Autrey, Tom; Barale, Jussara; Baricco, Marcello; Brooks, Kriston; Chalkiadakis, Nikolaos; Charbonnier, Véronique; Christensen, Steven; Bellosta von Colbe, José; et al.
Abstract: Industrial and public interest in hydrogen technologies has risen strongly recently, as hydrogen is the ideal means for medium to long term energy storage, transport and usage in combination with renewable and green energy supply. In a future energy system, the production, storage and usage of green hydrogen is a key technology. Hydrogen is and will in future be even more used for industrial production processes as a reduction agent or for the production of synthetic hydrocarbons, especially in the chemical industry and in refineries. Under certain conditions material based systems for hydrogen storage and compression offer advantages over the classical systems based on gaseous or liquid hydrogen. This includes in particular lower maintenance costs, higher reliability and safety. Hydrogen storage is possible at pressures and temperatures much closer to ambient conditions. Hydrogen compression is possible without any moving parts and only by using waste heat. In this paper, we summarize the newest developments of hydrogen carriers for storage and compression and in addition, give an overview of the different research activities in this field.